Development of an Integrated Physics Learning Module Using Augmented Reality (AR) with Al-Qur'an on Fluid Material for Senior High School - Enni Yusnita Firdaus; Sri Maiyena; Hadiyati Idrus; Venny Haris (Jurnal Ilmiah Pendidikan Fisika, 2023)
Teachers' Teaching materials are still limited, such as simple worksheets or textbooks. The available teaching materials are not yet integrated with the verses of the Qur'an and are not technology-based. One of the technologies currently being developed is Augmented Reality (AR) which can convert 2D images into 3D ones. AR is an innovation used to reduce the weaknesses of books and e-learning and can assist in visualizing things. Therefore, developing an integrated physics learning module using Augmented Reality with Al-Qur'an verses on fluid material is necessary. The type of development research used was the 4-D model, namely definition, design, development, and dissemination. However, this study is only in the development stage with limited trials. This study aims to produce an integrated physics learning module using AR based on Al-Qur'an on fluid material for senior high school that is valid and practical. Validation was obtained from some aspects, which are contents, media, and Al-Qur'an interpretation. The results showed that this module is very valid based on these three aspects (92% for contents, 83% for media, and 92% for Al-Qur'an interpretation). Practicality was obtained by a limited trial with students and physics teachers of MAN 2 Payakumbuh. The results obtained in this study are 89% for students and 91% for teachers. It means that this module is very practical. So, this module is very valid and practical for use in learning by teachers and students. From the results of this study, it can be concluded that the integrated physics learning module uses Augmented Reality with verses of the Qur'an in fluid material that meets the requirements with very good quality and is very suitable for use as a supporting teaching material in learning. The implications of this research will positively impact the development of Physics learning media in the future; using media learning based on augmented reality (AR) can provide information for educators on how to use appropriate learning media in the learning process.